2014
DOI: 10.21608/asjs.2014.179113
|View full text |Cite
|
Sign up to set email alerts
|

Hernia sac of indirect inguinal hernia: Invagination, excision or ligation?

Abstract: This study compares the effect of invaginating, excision of hernia sac without ligation with the traditional method of high ligation of the hernia sac on post-operative pain and recurrence.Patients and methods: This multicenter prospective randomized study included 152 patients with 167 primary indirect inguinal hernias. In group I (54 hernias) the sac was not opened and was inverted with the finger into the peritoneal cavity. In group E (56 hernias) the sac was excised at the neck without ligation. In group L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Chai et al [ 8 ] concluded that there was no difference in terms of recurrence between the sac transaction and sac reduction groups, which is similar to our findings. Regarding postoperative pain, Othman et al [ 37 ] compared the effect of invagination excision of the hernia sac without ligation with the traditional method of high ligation of the hernia sac on postoperative pain and recurrence. The authors found that invagination and excision of the hernia sac were safe and suitable for repairing sliding hernias without any adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Chai et al [ 8 ] concluded that there was no difference in terms of recurrence between the sac transaction and sac reduction groups, which is similar to our findings. Regarding postoperative pain, Othman et al [ 37 ] compared the effect of invagination excision of the hernia sac without ligation with the traditional method of high ligation of the hernia sac on postoperative pain and recurrence. The authors found that invagination and excision of the hernia sac were safe and suitable for repairing sliding hernias without any adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there are states of joy, inner satisfaction, and happiness that arise from many situations, such as success, wealth, health, and others. On the contrary, there are cases of suffering and pain that culminate in a sense of alienation and separation from social life as a result of the shock of death or disease (Osman, Abdel-Fattah, 2004).…”
Section: The Concept Of Social Workers' Attitudesmentioning
confidence: 99%